CAZRI Gum Inducer for Gum Production from Acacia senegal: Potential and SWOT Analysis - Krishnan, P Ratha; Tewari, J C; Bhati, T K (Annals of Arid Zone, 2016)
The technique of increased gum Arabic production from Acacia senegal using CAZRI gum inducer is a popular and well accepted strategy among the rural folk of Indian arid zone. It was evident the increased demand for the CAZRI gum inducer (ethephon) over years for the gum Arabic production in arid Rajasthan. Central Arid Zone Research Institute, Jodhpur, is the sole supplier of CAZRI gum inducer, therefore the increased sale trends revealed its acceptance and wide adaptability. It was also reflected by the increased sale of A. senegal seedlings from CAZRI for field planting. This paper summarizes the efforts to develop participatory mode of increased gum production and its SWOT (Strength, Weakness, Opportunity and Threats) analysis in the villages, where this technology was not known to the farmers. The analysis revealed the success of participatory gum production technology by win-win situation to all its stakeholders. The success of gum exudation depends on proper utilization of this technique. Hence, decentralized availability of gum inducer through any authorized distribution system is desirable to ensure the lateral spread of CAZRI’s proven technology, which also assures the distribution of quality gum Arabic inducer at a low price. Key words: Acacia senegal, gum inducer, participatory, SWOT analysis, technology.